Bintulu Development Authority (BDA) / Nurulain Ibrahim - Ibrahim, Nurulain (University Technology MARA Sarawak, 2012)
5S is being introduced in Japan by Dr Tuchiya and it is initiated for the first in Singapore during 1986. At the same time, 5S being introduced in Malaysia, Thailand, Korea, China, India, Indonesia, Sri Lanka, Russia, Hungary, Poland, Bulgaria, Columbia, Uruguay, Brazil, Costa Rica and Mexico (Universiti Tun Husein Onn Malaysia, 2009). 5S concept was being popularized and practiced by the Japan society. It is a methodology of creation and maintaining well organized, highly effective and high quality of workplace. It is the continuous improvement of work environment, quality, and safety in the work place (Michalska, 2007). 5S is the initial of 5 words from Japan which is followed by American word then, which is Seiri mean sorting, Seiton means set in order, Seiso means Shine, Seiketsu means standardize, and Shitsuke means sustaining the workplace (Wikipedia, 2012). It is being initialized to five key points that is more focus to a comprehensive quality environment. Besides, 5S concept gives benefit to make work easy, more organize and efficient.